2021
DOI: 10.1177/00033197211042684
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and Anti-Angiogenic Factors: Their Relevance in Diabetic Foot Syndrome—A Review

Abstract: Peripheral arterial disease can involve tissue loss in up to 50% of patients with diabetic foot syndrome (DFS). Consequently, revascularization of narrowed or occluded arteries is one of the most common forms of comprehensive treatment. However, technically successful angioplasty does not always result in the healing of ulcers. The pathomechanism of this phenomenon is still not fully understood, but inadequate angiogenesis in tissue repair may play an essential role. Changes in pro- and anti-angiogenic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 107 publications
0
7
0
1
Order By: Relevance
“…Previous animal and human studies in patients without and with diabetes in revascularization following ischemia have reported decreased expression of different pro-angiogenic factors, including VEGF-A, VEGFR-2, PDGF-B, PDGFR-β and HIF-1α in the diseased population 35 . VEGF is one of the main regulators of angiogenesis, activating different EC function such as cell migration, proliferation, and survival to enable the formation of new vessels and restore oxygenation of the limb following ischemia.…”
Section: Discussionmentioning
confidence: 90%
“…Previous animal and human studies in patients without and with diabetes in revascularization following ischemia have reported decreased expression of different pro-angiogenic factors, including VEGF-A, VEGFR-2, PDGF-B, PDGFR-β and HIF-1α in the diseased population 35 . VEGF is one of the main regulators of angiogenesis, activating different EC function such as cell migration, proliferation, and survival to enable the formation of new vessels and restore oxygenation of the limb following ischemia.…”
Section: Discussionmentioning
confidence: 90%
“…These factors increase the complexity of treatment and are associated with a worse prognosis. 93 epidemiology PAD is highly prevalent in diabetic patients, affecting approximately 25% of those aged > 60 years. 94 Stoberock et al 95 found that the prevalence of PAD varies from 20%-50% and 10%-26% in people with and without diabetes, respectively.…”
Section: Chapter 4 the Diabetic Foot And Peripheral Arterial Disease ...mentioning
confidence: 99%
“…O diabetes é um forte fator de risco para DAP, com desenvolvimento de uma doença arterial mais difusa, multissegmentar e de predomínio distal. Esses fatores aumentam a complexidade do tratamento e estão associados a pior prognóstico dos pacientes 93 .…”
Section: Introductionunclassified
“…This suggests that increased angiogenesis plays a critical role in normal wound healing during the early phase, but attenuation of angiogenesis is needed for proper healing. However, this dynamic regulation of angiogenesis may alter during diabetes due to changes in the expression levels of pro-and anti-angiogenesis proteins ( Figure 2 ), however, the available literature is not conclusive [ 25 ]. The inconsistencies between the results of the expression of pro-and anti-angiogenic factors may be due to loss of tissue, presence of necrosis and gangrene, the differential response of fibroblasts to hypoxia, different levels of inflammation, tissue fibrosis, vascular thrombosis, arteriolar sclerosis, differential expression of these mediators in different cells in healthy versus wound tissues and healthy versus diabetic tissue as well as different levels of hyperglycemia.…”
Section: Angiogenesis and Wound Healingmentioning
confidence: 99%
“…Another issue may be a differential expression between different types of diabetic ulcers. Difficulties in translating the lab findings to therapy in clinics to improve angiogenesis and wound healing are also due to the differential expression of these mediators in human versus murine models [ 25 ]. Temporary hypoxia is needed for angiogenesis as increased expression of HIF-1α dimerizes and activates hypoxia response elements causing increased expression of VEGF, but the presence of hyperglycemia affects the stability and activation of HIF-1α and attenuates angiogenesis through suppression of PDGF, VEGF, and TGF-β [ 26 ].…”
Section: Angiogenesis and Wound Healingmentioning
confidence: 99%